Effect of Herbicide Application on Weed Density and Yield of Wet Direct Seeded Spring Rice at Sundarpur, Nepal - Pant, Chudamani; Dhakal, Suman; Sah, Shrawan Kumar; Karkee, Suraj Singh (Agronomy Journal of Nepal, 2023)
Weeds are the major challenges for Direct Seeded Rice (DSR). A field experiment was carried out to evaluate the effect of herbicide application on weed density and yield of wet-direct seeded spring rice using Randomized Complete Block Design (RCBD), each treatment replicated thrice. The treatments consisted of three sole applications of pre-emergence herbicides (Pendimethalin @1000g a.i per ha, Pretilachlor @600g a.i ha-1 and Butachlor 1500 g a.i ha-1 at 3 DAS), six sequential applications of herbicides pre (at 3 DAS) and post emergence herbicides (at 22 DAS) (Pendimethalin fb Bispyibac Na @1000 fb 25 g a.i. ha-1, Pretialchlor fb Bispyibac Na @ 600 fb 25 g a.i. ha-1, Butachlor fb Bispyibac Na @ 1500 fb 25 g a.i. ha-1, Pendimethalin fb 2,4-D EE @1000 fb 500 g a.i. ha-1, Pretialchlor fb 2,4-D EE @600 fb 500 g a.i. ha-1, Butachlor fb 2,4-D EE @1500 fb 500 g a.i. ha-1) and two controls (weed free and weedy check). Result revealed that herbicide application significantly reduced the weed density (35.15-86.28%) compared with weedy check. Sequential application of pre and post emergence herbicides were more effective in reducing weed density and dry weight compared to sole application of herbicide. And among all sequential application, Pendimethalin fb Bispyribac sodium (119.3 m-2 and 124.33 m-2) and Butachlor fb Bispyribac sodium (129.3 m-2  and 148.0 m-2) were better and reduced weed density higher than other sequential application at 30 DAS and 90 DAS, whereas at 60 DAS, the highest reduction in total weed density was observed in Pretilachlor fb 2,4-D EE (90.0 m-2) and Butachlor fb Bispyribac sodium (93.0 m-2). The higher grain yield was observed in sequential application of pre-emergence herbicides followed byBispyribac sodium and was statistically similar with weed free plot. Up to 55.70% yield reduction was observed due to weeds. Therefore, sequential application of pre and post emergence herbicides: Pendimethalin fb Bispyribac sodium, Butachlor fb Bispyribac sodium and Pretilachlor fb Bispyribac sodium seems better in terms of reducing weed density and producing higher grain yield in wet-direct seeded spring rice.